Taking into account water use impacts in the LCA of biofuels an Argentinean case study. - Emmenegger, Mireille Faist (The International Journal of Life Cycle Assessment)
Purpose The assessment of biofuels has until now mainly focused on energy demand and greenhouse gas emissions. Only little attention has been given to other impacts, although the general importance of water use for the life cycle assessment (LCA) of agricultural products has been recognized in recent publications. The aim of this work is to assess in detail the water consumption along a biofuel production chain taking into account irrigation efficiencies, levels of water scarcity, and type of feedstock, and to integrate those results in a full LCA. Furthermore, we compare the results for biofuels from various feedstocks and regions with conventional petrol. Methods We calculate the water consumption and overall life cycle assessment results in a case study for the production of methyl ester from irrigated and non irrigated rapeseed. The results are compared with other irrigated and non irrigated biofuels based on different feedstocks. Results and discussion Water consumption in biofuel production chains based on non irrigated crops does not vary greatly and is in the same range as for fossil fuel. In contrast, as a consequence of irrigation, agricultural water consumption dominates the overall results of all irrigated crops. Consequently, the level of water scarcity plays a key role for the LCA results. In our case study, the environmental impacts of methyl ester from irrigated rapeseed in a water scarce region, measured in aggregated Eco-Indicator 99 scores, are almost doubled by water consumption. Variations in irrigation efficiency, however, are of little influence on the results, as the assessment method used here is based on consumptive water, which depends mainly on the evapotranspiration of the crop. Conclusions The focus on greenhouse gas emissions of the main regulatory schemes neglects other relevant environmental impacts and may provide the wrong incentives. Water consumption may thus become a major concern, offsetting the benefits of biofuel use with respect to climate change.